2001
DOI: 10.1080/152873901750128380
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Sodium Azide on Brain and Muscle Cytochrome Oxidase Activity: A Potential Model to Investigate Environmental Contributions to Neurodegenerative Diseases

Abstract: Deficits in oxidative phosphorylation have been implicated in many neurodegenerative diseases. In this study, cytochrome oxidase activity was inhibited following a 28-d systemic administration of nonlethal sodium azide via subcutaneous osmotic pumps. Quantitative enzyme histochemistry was performed on tissue sections from brain, skeletal muscle, and heart to localize cytochrome oxidase activity both globally and in regions within each tissue. Significant decreases of cytochrome oxidase activity were found in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…For example, it has been shown that sodium azide decreases cytochrome oxidase activity when chronically administered to rats (Cada et al 1995;Berndt et al 2001) and causes spatial memory deficits in rats tested in the Morris water maze (Bennett et al 1996) and the holeboard maze (Callaway et al 2002). Remarkably, when MB is administered to rats with reduced brain cytochrome oxidase activity, their memory retention scores are raised to the same level as that of control animals (Callaway et al 2002).…”
Section: Mb Increases Overall Brain Oxidative Metabolismmentioning
confidence: 80%
“…For example, it has been shown that sodium azide decreases cytochrome oxidase activity when chronically administered to rats (Cada et al 1995;Berndt et al 2001) and causes spatial memory deficits in rats tested in the Morris water maze (Bennett et al 1996) and the holeboard maze (Callaway et al 2002). Remarkably, when MB is administered to rats with reduced brain cytochrome oxidase activity, their memory retention scores are raised to the same level as that of control animals (Callaway et al 2002).…”
Section: Mb Increases Overall Brain Oxidative Metabolismmentioning
confidence: 80%
“…Altered mitochondrial fluidity and the activity of mitochondrial cytochrome c oxidase, which is the terminal oxidase in the respiratory chain, have been reported to be low in the AD brains (Parker, 1991;Sims, 1996;Maurer et al, 2000). Furthermore, a correlation was reported between decreased cytochrome c oxidase activity and deficits in cognitive abilities (Cada et al, 1995;Agin et al, 2001;Berndt et al, 2001). Nevertheless, the mechanisms related to the impairment of mitochondrial functions specific to AD remain unclear.…”
Section: Introductionmentioning
confidence: 97%
“…MnSOD activity was measured from mitochondrial extracts in the presence of 5 mM KCN to inhibit any contaminating CuZn SOD. Protocols for measuring cellular protein content, lactate concentration in the culture media, and whole cell respiration were as previously described (16).…”
Section: Methodsmentioning
confidence: 99%
“…The mechanism(s) by which azide mediates these effects is unknown. Moreover, its potential relevance to COX deficiency observed in a more physiologically relevant context has not been evaluated despite previous reports of selective COX losses leading to Alzheimer's diseaselike symptoms in rats that had been chronically infused with sodium azide (15,16).…”
mentioning
confidence: 99%